Doing and writing qualitative research - Holliday, Adrian (SAGE Publications, 2016)
With a strong focus on using less traditional forms of data, the Third Edition provides a new perspective on issues such as the role of the researcher and the impact they have on data, and also considers the impact of social, cultural and political complexities across a range of disciplines